SSRIs FOR DEPRESSION IN CHILDREN - Sinniah, Shalani (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 BACKGROUND : The question about the safety of SSRI therapy for depression in children cause us to compare the data published and unpublished data on the risks and benefits of these drugs. METHODS : We performed a meta - analysis of data from randomized controlled trials that evaluated SSRIs and placebo in participants aged 5-18 years and were published in the peer -reviewed journal or were unpublished and included a review by the Committee on Safety of Medicines. The results include: recurrence , response to treatment , depressive symptom scores , serious sampig effects , suicidal behavior, and cessation of treatment because of side effects . RESULTS : Data from the two trials showed fluoxetine has a benefit- harm profile is good , and unpublished data lend support to the present invention. Published results from one experiment paroxetine and sertraline two experiments showed equivocal results or gain - loss profile weakly positive . However , in both cases , the addition of no published data showing that more risks than benefits. Data from the trials were not published of citalopram and venlafaxine showed gain - loss profile is not good . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: SSRI, depression, fluoxetine